f ( x ) = p x 3 + 7 x 2 + 1 4 x + q
g ( x ) = x 2 + 3 x + 2
g ( x ) f ( x ) = x + 4
Find the value of p x 3 + 5 x 2 − 2 x − q when x = 1
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Accuracy | 5/5 | Everything is correct except the method |
Readability | 5/5 | Proper latex and well structured answer |
Ingenuity | 5/5 | Doesn't require values of p and q |
Total | 15/15 | Perfect! Keep it up @Vinayak Srivastava ! |
Log in to reply
Thanks! But I am still waiting for a problem where there can be multiple approaches, it will have a lot of ingenious solutions!
Log in to reply
This problem actually does have multiple approaches. I based it on algebraic long division. Some people just multiply g(x) with (x+4) to get p and q, then substitute. There are many ways.
PURE GENIUS!!!!!!!!!
Log in to reply
Hmm actually I don't think this is "genius", tbh. This word is reserved for the greats(at least I think so).
Great solution! But I think you needed to write x2 + 3x + 2 instead of 4, in line 1.
Log in to reply
Done. Thanks!
Multiplying g ( x ) f ( x ) by g ( x ) , we have f ( x ) = ( x + 4 ) ( x 2 + 3 x + 2 ) . Because the degree of x + 4 is 1 , x 2 + 3 x + 2 is 2 , and the degree of f ( x ) is three, since 1 + 2 = 3 , then p is the multiple of the coefficients of the leading terms of g ( x ) f ( x ) and g ( x ) , which is 1 × 1 , which is equal to 1 . Since q has degree 0 , q is the multiple of the terms that have degree 0 in both g ( x ) and g ( x ) f ( x ) , which is 4 × 2 = 8 , so q is 8 . Because the output of a function a ( x ) when x is 1 is just the sum of of all the coefficients of the terms of the polynomial (because all the x n terms are just reduced to 1 ), we have 1 + 5 − 2 − 8 = − 4 , so the value of p x 3 + 5 x 2 − 2 x − q when x is one is − 4
At x=1
g ( x ) f ( x ) = ( 1 ) + 3 ( 1 ) + 2 ( 1 ) p ( 1 ) + 5 ( 1 ) + 2 ( 1 ) + 1 4 ( 1 ) + q = ( 1 ) + 4
This gives us ,
p + q = 9 -----(✪)
Now we'll take the functions again and play with 'em a lil,
~~~~~~~~~~~~~~~~~~~~~
p ∗ x 3 + 7 ∗ x 2 + 1 4 x + q = x 3 + 7 x 2 + 1 4 x + 8
~~~~~~~~~~~~~~~~~~~~~
Comparing the coefficients of x 3 and constants,we got to know that
p = 1 and q = 8
We can adjust the LHS according to our requirements by doing the following
~~~~~~~~~~~~~~~~~~~~~
p ∗ x 3 + 5 ∗ x 2 + 2 ∗ x 2 − 2 x + 1 6 x − q + 2 q = x 3 + 7 x 2 + 1 4 x + 8
~~~~~~~~~~~~~~~~~~~~~
Shifting the unwanted part to RHS we get,
~~~~~~~~~~~~~~~~~~~~~
p ∗ x 3 + 5 ∗ x 2 − 2 x − q = x 3 + 7 x 2 − 2 x 2 + 1 4 x − 1 6 x + 8 − 2 q
~~~~~~~~~~~~~~~~~~~~~
Substituting x=1 in the modified version of the equations we get,
~~~~~~~~~~~~~~~~~~~~~
p ∗ x 3 + 5 ∗ x 2 − 2 x − q = 1 + 5 − 2 + 8 − 2 ( 8 ) = − 4
~~~~~~~~~~~~~~~~~~~~~
Hence − 4 is the correct answer!
FYI:U can also use turquoise,cyan,forest green,crimson,lime,Persian blue,violet in ur latex code!
When
x
=
−
1
, we have
f
(
−
1
)
=
−
p
+
7
−
1
4
+
q
=
−
p
+
q
−
7
and
f
(
−
1
)
=
g
(
−
1
)
×
g
(
−
1
)
f
(
−
1
)
=
(
1
−
3
+
2
)
×
(
−
1
+
4
)
=
0
.
∴
−
p
+
q
−
7
=
0
.
Solve to get
p
−
q
=
−
7
.
∴
When
x
=
1
,
p
x
3
+
5
x
2
−
2
x
−
q
=
p
+
5
−
2
−
q
=
(
p
−
q
)
+
(
5
−
2
)
=
−
7
+
3
=
−
4
.
p x 3 + 5 x 2 − 2 x − q = f ( x ) − 2 x 2 − 1 6 x − 2 q = g ( x ) f ( x ) ⋅ g ( x ) − 2 x 2 − 1 6 x
When x = 1: g ( x ) = ( 1 ) 2 + 3 ( 1 ) + 2 = 1 + 3 + 2 = 6
g ( x ) f ( x ) = 1 + 4 = 5
2 x 2 = 2 ( 1 ) 2 = 2 ( 1 ) = 2
1 6 x = 1 6 ( 1 ) = 1 6
Also, since q is a constant, it will be the product of the constants in g ( x ) , and g ( x ) f ( x ) (Also because there is no term with the power of x − 1 or lower ) .
∴ q = 2 ⋅ 4 = 8 , 2 q = 1 6
p x 3 + 5 x 2 − 2 x − q = ( 5 ⋅ 6 ) − 2 − 1 6 − 1 6 = 3 0 − 3 4 = − 4
f ( x ) = g ( x ) f ( x ) ⋅ g ( x ) = ( x 2 + 3 x + 2 ) ( x + 4 )
= ( x 2 ) ( x ) + ( x 2 ) ( 4 ) + ( 3 x ) ( x ) + ( 3 x ) ( 4 ) + ( 2 ) ( x ) + ( 2 ) ( 4 ) = x 3 + 4 x 2 + 3 x 2 + 1 2 x + 2 x + 8 = x 3 + 7 x 2 + 1 4 x + 8
∴ p = 1 , q = 8
p x 3 + 5 x 2 − 2 x − q = x 3 + 5 x 2 − 2 x − 8 = ( 1 ) 3 + 5 ( 1 ) 2 − 2 ( 1 ) − 8 = 1 + 5 − 2 − 8 = 6 − 1 0 = − 4
f(x) = g(x) * (x + 4) = (x^2+3x+2) * (x+4) = x^3 + 7x^2 + 14x + 8. Comparing with the given expression for f(x), we find p = 1 and q = 8. Then , px^3 + 5x^2 -2x - q = (1)(1)^3 + 5(1)^2 - 2(1) - 8 = 6 - 10 = -4
The third equation implies that f ( x ) = g ( x ) ( x + 4 ) = ( x 2 + 3 x + 2 ) ( x + 4 ) f ( x ) = p x 3 + 7 x 2 + 1 4 x + q 1 ⋅ x 3 + 8 = x 3 + 7 x 2 + 1 4 x + 8 = x 3 + 7 x 2 + 1 4 x + 8 ∣ − 7 x ² − 1 4 x = p ⋅ x 2 + q ⟺ p = 1 , q = 8 Plugging x = p = 1 and q = 8 in the equation, we get 1 + 5 − 2 − 8 = 6 − 1 0 = − 4 .
PS: Shoutout to Vinayak Srivastava, your approach is killer!
g ( x ) = x ² + 3 x + 2 = x ² + x + 2 x + 2 = x ( x + 1 ) + 2 ( x + 1 ) = ( x + 1 ) ( x + 2 )
Given
g
(
x
)
p
(
x
)
p
(
x
)
p
(
x
)
=
x
+
4
=
g
(
x
)
(
x
+
4
)
=
(
x
+
1
)
(
x
+
2
)
(
x
+
4
)
Now the coefficient of x³ is the product of coefficient of each x in p(x)'s factorization, therefore p = 1×1×1 = 1
And q = product of constants in p(x)'s factorization = 1×2×4 = 8
Then we get, px³+5x²-2x-q = x³+5x²-2x-8
Now substitute x = 1, The value becomes 1+5-2-8 = -4
First, we need to find the value of p and q . f ( x ) = g ( x ) × ( x + 4 ) = ( x 2 + 3 x + 2 ) ( x + 4 ) = x 3 + 7 x 2 + 1 4 x = 8 → p = 1 , q = 8 . Now that we have got the values of p and q , p x 3 + 5 x 2 − 2 x − q = 1 × 1 3 + 5 × 1 2 − 2 × 1 − 8 = 1 + 5 − 2 − 8 = − 4
Since we know that g ( x ) f ( x ) = x + 4 and f ( x ) = p x 3 + 7 x 2 + 1 4 x + q and g ( x ) = x 2 + 3 x + 2 , g ( x ) f ( x ) = x 2 + 3 x + 2 p x 3 + 7 x 2 + 1 4 x + q = x + 4 . We then multiply to get p x 3 + 7 x 2 + 1 4 x + q = x 3 + 7 x 2 + 1 4 x + 8 with p = 1 and q = 8 . Now we plug in the values of p and q to get 1 ( 1 3 ) + 5 ( 1 2 ) − 2 ( 1 ) − 8 = 1 + 5 − 2 − 8 = 6 − 2 − 8 = 4 − 8 = − 4
The general form of a cubic polynomial is a x 3 + b x 2 + c x + d , we also know that multiplying a quadratic polynomial (one of degree 2 ) with a linear polynomial (one of degree 1 ) provides us with a cubic polynomial, i.e,
( a 1 x 2 + b 1 x + c 1 ) ( a 2 x + b 2 ) = a x 3 + b x 2 + c x + d
( a 1 a 2 ) x 3 + ( a 1 b 2 + b 1 a 2 ) x 2 + ( c 1 a 2 + b 1 b 2 ) x + ( c 1 b 2 ) = a x 3 + b x 2 + c x + d
Where a = a 1 a 2 , b = a 1 b 2 + b 1 a 2 , c = c 1 a 2 + b 1 b 2 and d = c 1 b 2 by observation of coefficients.
We're here given a cubic polynomial f ( x ) = p x 3 + 7 x 2 + 1 4 x + q , which when divided by a quadratic polynomial g ( x ) = x 2 + 3 x + 2 , gets divided totally and gives the quotient, a linear polynomial, x + 4 , now
g ( x ) f ( x ) = ( x + 4 ) ⇒ f ( x ) = g ( x ) ( x + 4 )
Thus f ( x ) is the product of g ( x ) , a quadratic polynomial, and ( x + 4 ) , a linear polynomial, it follows by our above discussion that p = 1 × 1 = 1 and q = 4 × 2 = 8 , which gives the third polynomial with no name, p x 3 + 5 x 2 − 2 x − q as,
N ( x ) = 1 x 3 + 5 x 2 − 2 x − 8
We're assigned to find the value of N ( x ) at x = 1 , i.e, N ( 1 ) , which gives us,
N ( 1 ) = 1 ( 1 ) 3 + 5 ( 1 ) 2 − 2 ( 1 ) − 8 = − 4
Hey Percy, not gonna put down the common solution? (I broke the unwanted streak completely)
I will...once I post all the problems...
Let p ( x ) be p x 3 + 5 x 2 − 2 x − q
f ( x ) = p x 3 + 7 x 2 + 1 4 x + q … ( 1 )
g ( x ) = x 2 + 3 x + 2 … ( 2 )
g ( x ) f ( x ) = x + 4
⇒ f ( x ) = ( x + 4 ) ( g ( x ) )
= ( x + 4 ) ( x 2 + 3 x + 2 ) [ Using ( 2 ) ]
= x 3 + 7 x 2 + 1 4 x + 8 … ( 3 )
We get eq.(1) = eq.(3)
By comparing them we get, p = 1 and q = 8
p ( 1 ) = 1 ( 1 ) 3 + 5 ( 1 ) 2 − 2 ( 1 ) − 8 → p ( 1 ) = 1 + 5 − 2 − 8 → p ( 1 ) = − 4
∴ The answer is − 4
Simplifying what we have to find as much as we can:
Substitute x = 1
p x 3 + 5 x 2 − 2 x − q = p + 5 − 2 − q = p − q + 3 .....(eqn1)
So the unknown part is p − q . Consider f ( x ) = p x 3 + 7 x 2 + 1 4 x + q We have to find the value of p − q ( ( − p + q ) will also work ). In f ( x ) we cannot change the sign of q . Since any value of x will satisfy given conditions, we have to choose it wisely so that the value of p x 3 in f(x) will be − p . Simply Logic tells us that the necessary value of x = − 1 . Also from given it is obvious that f ( x ) = g ( x ) ∗ ( x + 4 )
Substituting x = − 1 in f ( x ) = g ( x ) ∗ ( x + 4 )
− p + 7 − 1 4 + q = ( 1 − 3 + 2 ) ( − 1 + 4 )
p − q = − 7
Substituting in eqn1:
-7+3 = - 4
Alternative (lengthy) method
Though this is Lengthy it is easier to spot (if you know what I mean) and also gives you the values of p and q (which is not necessary but anyways)
g ( x ) f ( x ) = x 2 + 3 x + 2 p x 3 + 7 x 2 + 1 4 x + q = x + 4 .....(eqn1)
Now, this is true for every value of x .
So, let's just put x = 0 in (eqn1). (In other words lets just forget the terms with x )
2 q = 4
q = 8
Substitute q = 8 and this time x = 1 in (eqn1)
1 + 3 + 2 p + 7 + 1 4 + 8 = 1 + 4
6 p + 2 9 = 5
p = 3 0 − 2 9
p = 1
p = 1 a n d q = 8
Simple calculations show: p x 3 + 5 x 2 − 2 x − q when x = 1 ; p = 1 ; q = 8 is - 4
@Percy Jackson , I just saw that @Siddhesh Umarjee has also shown the same method, and he posted it before me, so I think the ingenuity points should go to him rather than me.
Log in to reply
The common solution is multiplying g(x) by (x+4), then finding values of p and q and substituting. Since due to timezones and stuff not everyone can post early, everyone who gave this solution will get ingenuity points, because I think all three solutions have been explained well and show your knowledge of the concept. That is what ingenuity is about :)
@Zakir Husain also used the same method and posted before me but I believe everyone who used that method should get ingenuity points taking into consideration the time zones and the fact the the Questions were not posted at a predetermined time( @Percy Jackson and @Jason Gomez no offence... you guys are doing a fantastic job) but it is the judge's decision...
Log in to reply
Oh yeah, I see. But 3 people used same method so it is common solution lol
Yea, you're right. No offense taken, I know how disorganized I can be :P
∵ g ( x ) f ( x ) = x + 4 ∴ f ( x ) = ( x + 4 ) g ( x ) = ( x + 4 ) ( x 2 + 3 x + 2 ) M e t h o d 1 i f x = − 1 ⇒ f ( − 1 ) = ( − 1 + 4 ) ( ( − 1 ) 2 − 3 + 2 ) = 0 ⇒ − p + 7 − 1 4 + q = 0 ⇒ p − q = 7 − 1 4 = − 7 p × ( 1 ) 3 + 5 × ( 1 ) 2 − 2 × ( 1 ) − q = p + 5 − 2 − q p − q + 3 = − 7 + 3 = − 4 M e t h o d 2 f ( x ) = ( x + 4 ) g ( x ) ⇒ f ( − 4 ) = 0 ⇒ − 6 4 p + 1 1 2 − 5 6 + q = 0 ⇒ 6 4 p − q = 5 6 . . . . . . . . . . [ 1 ] ∵ g ( − 2 ) = 0 J u s t p u t a n d f i n d , y o u w i l l g e t 0 ⇒ f ( − 2 ) = 0 ⇒ − 8 p + 2 8 − 2 8 + q = 0 ⇒ 8 p = q . . . . . . . . . . [ 2 ] [ 1 ] a n d [ 2 ] ⇒ 6 4 p − 8 p = 5 6 ⇒ p = 1 , q = 8 ⇒ p × ( 1 ) 3 + 5 × ( 1 ) 2 − 2 × ( 1 ) − q = 1 + 5 − 2 − 8 = 6 − 1 0 = − 4
Problem Loading...
Note Loading...
Set Loading...
Let's solve it without calculating p or q
⟹ ⟹ ⟹ Let ⟹ f ( x ) = g ( x ) ( x + 4 ) = ( x 2 + 3 x + 2 ) ( x + 4 ) f ( − 1 ) = 0 − p + 7 − 1 4 + q = 0 p − q = − 7 k ( x ) = p x 3 + 5 x 2 − 2 x − q k ( 1 ) = p + 5 − 2 − q = ( p − q ) + 3 = − 7 + 3 = − 4